2002
DOI: 10.1097/00005537-200209000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma–Cyclin‐Dependent Kinase Pathway Deregulation in Vestibular Schwannomas

Abstract: The pRb-CDK pathway was altered in all vestibular schwannoma tumors examined, with CDK2 significantly downregulated in seven of the eight tumors. Further investigation into the regulatory mechanisms governing CDK2 expression may lead to a better understanding of vestibular schwannoma tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The retinoblastoma protein (pRb) is encoded by the RB1 gene. Lasak et al [84] examined a deregulated signaling pathway, the retinoblastoma protein (pRb)-cyclin-dependent kinase (CDK) pathway, which was downregulated in 7 of 8 tumors. This signaling pathway is involved in the G1 to S cell cycle progression, promoting cell proliferation.…”
Section: Deregulated Genes In Vestibular Schwannomamentioning
confidence: 99%
See 1 more Smart Citation
“…The retinoblastoma protein (pRb) is encoded by the RB1 gene. Lasak et al [84] examined a deregulated signaling pathway, the retinoblastoma protein (pRb)-cyclin-dependent kinase (CDK) pathway, which was downregulated in 7 of 8 tumors. This signaling pathway is involved in the G1 to S cell cycle progression, promoting cell proliferation.…”
Section: Deregulated Genes In Vestibular Schwannomamentioning
confidence: 99%
“…This signaling pathway is involved in the G1 to S cell cycle progression, promoting cell proliferation. As already stated by Cayé-Thomasen et al [23], the available data for the CDK pathway is conflicting, since one group found downregulation [84] while the other found upregulation [23]. Gonzalez-Gomez et al [22] had previously suggested an inverse link between the methylation of RB1 and p16 INK4a (found in 15% of samples) and cell cycle regulation, with the latter being altered through epigenetic changes.…”
Section: Deregulated Genes In Vestibular Schwannomamentioning
confidence: 99%
“…Several studies have suggested an interaction between merlin and cell-cycle regulation via the pRb-CDK pathway. 13 Lasak and colleagues 17 have used microarray technology to study the G 1 to S phase cell-cycle pathway in VS tissue. Microarray chips with a large number of genes known to be important to the pRb-CDK pathway were generated and hybridized to cDNA from VS.…”
Section: Radiation and Cell-cycle Checkpoint Regulationmentioning
confidence: 99%
“…Epigenetic changes have also been described in several genes, some of them with clinical implications on VS behavior (2). In addition to different mechanisms of gene inactivation, deregulated expression of growth regulatory genes may also play a role in the VS tumorigenesis (3). It has been shown that cyclin D1 is a key cell-cycle regulatory protein for the mammalian G1-S phase transition and is involved in the regulation of proliferation and differentiation.…”
mentioning
confidence: 99%